La importancia de contar con las normas internacionales de control de calidad NICC 1 en los procesos de revisoría fiscal dentro de las organizaciones (2023)
As a starting point, it is important to understand international quality control standards from their inception. The International Standards Committee (IASC) was the first precursor that proposed the relevant IASC 1, whose purpose is to establish a quality control system for auditing firms that provide auditing services and reviews of financial statements. The purpose is to get to know the standard through its historical context, highlight its importance, mention in detail its elements, principles and characteristics at international level.